2021
DOI: 10.1007/s40617-021-00603-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telehealth Direct Therapy for Individuals with Autism Spectrum Disorder

Abstract: The field of applied behavior analysis (ABA) has utilized telehealth for clinical supervision and caregiver guidance with research supporting the use of both modalities. Research demonstrating effectiveness is crucial, as behavior analysts must ensure the services they provide are effective in order to be ethical. With the increased need for patients to access more services via telehealth, due to the novel coronavirus (COVID-19) pandemic, the current study evaluated the efficacy of telehealth direct therapy to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…Guidelines by CASP ( 2020 ), Rodriguez ( 2020 ), and Nohelty, Hirschfeld, and Miyake ( 2021 ) mentioned that reinforcers should be used during telehealth direct sessions, but no detailed considerations were given. Similarly, other studies on telehealth direct ABA services did not specify the type of reinforcers used in their studies (Cihon et al, 2021 ; Pellegrino & DiGennaro Reed, 2020 ; Pollard et al, 2021 ) with an exception of Ferguson et al ( 2020 ) and Nohelty, Bradford, et al ( 2021 ). Ferguson et al noted that they used only verbal praise for correct responses and suggested that future studies explore whether other types of stimuli such as edibles and tangibles would serve as reinforcers via telehealth.…”
Section: Preference Assessments and Reinforcers—practice Recommendationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Guidelines by CASP ( 2020 ), Rodriguez ( 2020 ), and Nohelty, Hirschfeld, and Miyake ( 2021 ) mentioned that reinforcers should be used during telehealth direct sessions, but no detailed considerations were given. Similarly, other studies on telehealth direct ABA services did not specify the type of reinforcers used in their studies (Cihon et al, 2021 ; Pellegrino & DiGennaro Reed, 2020 ; Pollard et al, 2021 ) with an exception of Ferguson et al ( 2020 ) and Nohelty, Bradford, et al ( 2021 ). Ferguson et al noted that they used only verbal praise for correct responses and suggested that future studies explore whether other types of stimuli such as edibles and tangibles would serve as reinforcers via telehealth.…”
Section: Preference Assessments and Reinforcers—practice Recommendationsmentioning
confidence: 97%
“…For example, CASP ( 2020 ) suggested the following models: telehealth direct service (a technician delivers treatment to a client via real-time videoconferencing), partial telehealth model (a technician or caregiver delivers treatment in-person while supervised by a clinician via telehealth), caregiver-implemented service (a caregiver is trained by a clinician via telehealth to deliver ABA treatment protocols on their own in-person; also referred to as parent-coaching model, Wacker et al, 2013 ), and caregiver training and consultation (a clinician meets with a parent to discuss general issues). Furthermore, Pollard et al ( 2021 ) and Nohelty, Bradford et al ( 2021 ) separated telehealth direct ABA service into three different models: (a) the technician-delivered telehealth service model, (b) the caregiver-assisted telehealth model, and (c) the caregiver-implemented telehealth model. In the technician-delivered telehealth service model, a practitioner is the one who provides all the instructions, prompts, reinforcers, and data collection without caregiver support.…”
Section: Aba Service Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Autism studies that have investigated the remote delivery (via videoconferencing) of direct psychological interventions not targeting mental health, but rather solely targeting functional skills, have likewise shown promise (e.g. Cihon et al, 2021 ; Ferguson et al, 2020 ; Ford, Wang, Koegel, Koegel, & Fedders, 2020 ; Nohelty, Bradford, Hirschfeld, Miyake, & Novack, 2021 ; Pollard, LeBlanc, Griffin, & Baker, 2021 ). These were conducted before and since the pandemic started, and the only challenges reported surrounded technological issues, at-home distractions, instructional control, and the need for parental support for some individuals.…”
Section: Introductionmentioning
confidence: 99%